Oceans 2007 2007
DOI: 10.1109/oceans.2007.4449344
|View full text |Cite
|
Sign up to set email alerts
|

Environmental equalizer for underwater communications

Abstract: This paper presents an environmental-based equalization algorithm for underwater communications. This algorithm is based on the passive time-reversal (pTR) and waveguide invariant properties of ocean channels. Passive time-reversal allows for the implementation of a simple communications system, but it loses performance in the presence of geometric mismatch between the probe-signal and the actual data symbols transmission. The waveguide invariant properties state that geometric mismatches, both in depth and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…For high SN R in ≈ −10 dB the residual ISI of the TR operator becomes dominant and leads to saturation of SN R mse . For high residual ISI, in the HF case, Figure 4(b) shows that for a low SN R in ≈ −25 dB good agreement in shape is obtained between the ideal pTR and MSE curves a better agreement would be obtained if instead of the SN R out given by (17) the SN R out given by (18) was used, nevertheless the agreement in shape its enough for the optimum time window length prediction. For high SN R in ≈ −10 dB the residual ISI of the TR operator becomes dominant and leads to saturation of SN R mse .…”
Section: Simulation Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…For high SN R in ≈ −10 dB the residual ISI of the TR operator becomes dominant and leads to saturation of SN R mse . For high residual ISI, in the HF case, Figure 4(b) shows that for a low SN R in ≈ −25 dB good agreement in shape is obtained between the ideal pTR and MSE curves a better agreement would be obtained if instead of the SN R out given by (17) the SN R out given by (18) was used, nevertheless the agreement in shape its enough for the optimum time window length prediction. For high SN R in ≈ −10 dB the residual ISI of the TR operator becomes dominant and leads to saturation of SN R mse .…”
Section: Simulation Resultsmentioning
confidence: 88%
“…Future developments should address the problem of using the proposed time-window optimization with adaptive pTR-based equalizers [17]. Up to now the proposed probe timing optimization method as been successfully applied with the pTR based environment equalizers presented in [18].…”
Section: Discussionmentioning
confidence: 99%
“…8 In current Doppler compensation techniques, Doppler distortion is compensated with a single value that fails to give maximum compensation. 9,10 In Silva et al, 11 an improved version of pTR frequency shift pTR (FSpTR) was proposed that includes appropriate frequency shifts in the pTR impulse response estimates so as to maximize the output power at each time instant during the interval between successive probes. It was proved with both simulated and real data that FSpTR could provide an MSE gain of several decibels and in Vilaipornsawai et al, 12 a DFE was integrated with FSpTR to improve the performance of the communication system.…”
Section: Introductionmentioning
confidence: 99%
“…This system is considered as a Single Input Multiple Output (SIMa) communication system. To address the time-varying channel effect, caused by a moving source/receiver, the geometry adapted pTR technique was proposed in [2], [3]. It was shown that by employing a frequency shifted version of the estimated channel impulse response in the pTR processing, geometric changes can be partially compensated.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that by employing a frequency shifted version of the estimated channel impulse response in the pTR processing, geometric changes can be partially compensated. Hence, the technique of [3] is referred to as Frequency Shift pTR 978-1-61284-4577-0088-0/11/$26.00 ©2011 IEEE (FSpTR). Although a pTR-based technique can mitigate the lSI problem, an equalizer is required to eliminate the residual lSI as shown theoretically in [4].…”
Section: Introductionmentioning
confidence: 99%